Assessment of Patient Knowledge and Perceptions of Pharmacogenomics Before and After Using a Mock Results Patient Web Portal - Tien M. Truong; Elizabeth Lipschultz; Keith Danahey; Emily Schierer; Mark J. Ratain; Peter H. O'Donnell (Wiley, 2020)
Our objective was to build a mock pharmacogenomic (PGx) patient portal and assess its ability to disseminate test results and information to patients. The YourPGx Portal delivered four sample PGx results (omeprazole, simvastatin, clopidogrel, and codeine). We hosted two study groups to assess patient knowledge and perceptions of PGx before and after accessing the portal. Ten PGx‐tested and 10 traditional care participants were included (average 61 years, 60% women, 50% African American, and 55% had a bachelor's/advanced degree). Participants scored significantly higher on the post‐test compared with the pre‐test, with no significant differences between baseline scores or score change between the groups. Patient perceptions also improved after accessing the portal-more patients wanted their providers to have access to test results, and more patients would encourage family/friends to get PGx testing. Patients would share their test results with their healthcare providers, spouse/partner, and family; none would share results with their friends or social media. Almost all patients (95%) said the portal was easy to use and 65% said it was easy to understand. In this pilot study, patients' knowledge and perceptions of PGx improved after accessing the YourPGx Portal.